ANALISIS PENGARUH PELAKSANAAN CSR TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI MEDIASI - William Gultom; Yunia Panjaitan (Prosiding Working Papers Series In Management, 2017)
Public demands for companies to conduct CSR has increased, but many companies have not done CSR activities, for they still consider CSR as an expense. A new concept says that CSR can be a potential investment to increase the value of the company. The purpose of this study is to determine the effect of CSR implementation on firm value with profitability as a mediation variable. The research method used in this study is path analysis method and simple linear regression analysis method, using SPSS version 23.0. The total sample used is 46 companies. The results of this study prove that the implementation of CSR through Profitability do not have influence to the Company Value. Keywords: Corporate Social Responsibility, Profitability, Company Value